Mineral and organic fertilizer combined with doses of Azospirillum brasilense in an orchid hybrid - Alves Netto, Leila; Villa, Fabíola; Fernandes da Silva, Daniel; Sabini da Silva, Luciana; Menegazzo da Silva, Giordana; Costa da Silva, Edvan (Comunicata Scientiae, 2021)
Orchid production requires careful management of the crop. The objective of this work was to evaluate the growth of transplanted seedlings of hybrid orchid Cattleya virginia x BrassoCattleya pastoral, added with Azospirillum brasilense and different sources of fertilization. The experiment was conducted in a private orchard in the municipality of Marechal Cândido Rondon (PR). The experimental design was a randomized complete block design, in a 2 x 4 factorial scheme (2 fertilization sources x 4 concentrations of A. brasilense), containing four replications with 5 plants per replicate, totaling 160 homogeneous seedlings, where the fertilization sources were Bokaschi® as a source of organic fertilizer and NPK in formulation 10-10-10 as a soluble mineral at the rates: C1 = 0 mL-1 water, C2 = 1.0 mL-1 water, C3 = 1.5 mL -1 of water and C4 = 2.0 mL-1 of water. After 10 months, phytotechnical evaluations were performed, such as total number of roots; length of the largest root; number of leaves; length and width of the largest sheet; number of pseudobulbs; number of shoots; diameter of the pseudobulb. The use of Masterfix Gramines® in the growth of the hybrid Cattleya virginia x BrassoCattleya pastoral, provided the increase in the diameter of the pseudobulb, the largest number of roots and the largest root length. The interaction of the addition of A. brasilense with mineral fertilization with NPK in the formulation 10-10-10 obtained the highest number of shoots.